Salinity’s Shadow: Sustainable Modular Resilience for the Munda Community, Satkhira (International Journal of Scientific Research and Management (IJSRM), 2024)
Bangladesh is gifted with abundant natural beauty, with rivers, woods, seas, plains, hills, haors, and canals. However, due to its tropical climate, it is prone to several natural calamities, including excessive salinity in coastal areas. Sundarban is one of these coastal areas where reside the Munda community which is one of the 33 ethnic groups of Bangladesh. Originating from India, Mundas are variously dependent on the Sundarbans for both livelihood and religious aspect and consider the Sundarbans as their mother nature. But poverty and calamities limit their participation in social activities and access to necessities like food, education, and healthcare. This paper aimed to evaluate the difficulties the Munda community faces due to salinity and create a modular structural system that was sympathetic to local culture and more cost-effective local resources that would be more resilient to natural disasters. This paper studied the lifestyle and livelihood of the affected munda community of Burigoalini, Satkhira. This paper finds the available construction materials’ quality and resilience in connection to saline impacts and local housing characteristics and also focuses on the historical, cultural, and existential aspects of an ethnic group that is facing the risk of extinction.